Determining the Optimal Cognitive Screening Tool in Older People With Diabetes - Mordenfeld, Nadia; Gayus, Noa; Azmon, Michal; Guri-Twito, Omri; Yahalom Peri, Tal; Natovich, Rachel; Cukierman-Yaffe, Tali (Frontiers in Endocrinology, 2020)
Background: Self-care is an important perspective to ageing and transitional states in diabetes management. Population studies have shown that lower cognitive function is associated with worse self-care abilities. Several guidelines have emphasized the importance of assessing cognitive function in older people with diabetes and tailoring treatment plan accordingly. Those guidelines do not specify which tools are the most appropriate for this population. One approach to delineate which tools should be used is to assess which tools best correlate with self-care capacity. Objective: To assess which cognitive assessment tools best correlate with self-care capacity in older people with type 2 diabetes. Methods: Cross-sectional study, conducted amongst individuals with diabetes over the age of 60. The association between self-care capacity indices and different cognitive assessment tools was examined. Principal Component self-care constructs were determined and the association between these and the different cognitive assessment tools was examined. Results: A significant association was found between the Principal Component self-care construct and the Montreal Cognitive Assessment and MindstreamsTM scores. In a stepwise regression model including only the Montreal Cognitive Assessment score, a significant association was found between this score and the Principal Component self-care construct. The same was not found in a model that included only the MindstreamsTM scores. Conclusions: The Montreal Cognitive Assessment, previously validated as a brief cognitive screening tool, may be useful as an adjunct to assess the self-care capacity of older individuals with diabetes. Future studies in the clinic are needed to evaluate if using this tool may improve treatment plans.